"All Hands-on Deck" - Marta Fortunato; António Moreira; Ana Raquel Simões (Universidade de Lisboa, 2022)
Supported by Chou's Octalysis Framework (2016) in the design of activities, this article investigates how Octalysis framework-based reading and writing activities can be conducive to foster the learning of reading and writing in English as a Foreign Language by primary education pupils in a collaborative project-based learning context. A case study was carried out in a third-grade classroom in a Portuguese private school. The sessions, developed in face-to-face and online modes, were organized according to pupils' answers to a questionnaire - to identify their learning preferences. Qualitative data, collected through sessions' audio and video recordings, pupils' assignments, group assessments, and cloze tests became the basis of this paper. Results revealed that pupils were motivated and engaged in performing reading and writing tasks, having improved their reading and writing skills, and also promoted the development of social and cognitive soft skills.